Control of immune cell signaling by the immuno-metabolite itaconate - Lang, Roland; Siddique, Md Nur A Alam (Frontiers in Immunology, 2024)
Abbreviations 4-OI 4-ocytl itaconate ACOD1 Aconitate decarboxylase 1 BMDM bone marrow-derived macrophages CLR C-type lectin receptor DMI dimethyl itaconate ECAR extracellular acidification rate FcγR Fc gamma receptor IFN interferon IRF interferon-regulatory factor IRG1 immune-response gene 1 ISG interferon-stimulated genes MDSC myeloid-derived suppressor cells MTB Mycobacterium tuberculosis OCR oxygen consumption rate PTM post-translational modification SDH succinate dehydrogenase TCA tricarboxylic acid cycle TLR toll-like receptor TNF tumor necrosis factor MTB Mycobacterium tuberculosis